2017
DOI: 10.1200/po.16.00038
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Rapid Autopsies Enable Tumor Evolution Tracking and Generation of Preclinical Models

Abstract: Purpose Patients with cancer who graciously consent for autopsy represent an invaluable resource for the study of cancer biology. To advance the study of tumor evolution, metastases, and resistance to treatment, we developed a next-generation rapid autopsy program integrated within a broader precision medicine clinical trial that interrogates pre- and postmortem tissue samples for patients of all ages and cancer types. Materials and Methods One hundred twenty-three (22%) of 554 patients who consented to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 38 publications
1
36
0
Order By: Relevance
“…Currently, the number of rapid autopsy programs (RAPs) in the United States is relatively small, and a few Cancer September 1, 2019 additional programs have been established in Canada, Australia, and, very recently, Europe. Some of these programs are focused on just 1 tumor type (eg, prostate cancer 9 ), whereas others accept a greater variety of patients. These programs may be directed by pathologists (usually), oncologists (frequently), or other researchers (occasionally), although pathologist involvement is always important for a properly executed autopsy procedure and for the selection of the best quality tissue for sampling.…”
Section: Organization Of Rapid Autopsy Programsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the number of rapid autopsy programs (RAPs) in the United States is relatively small, and a few Cancer September 1, 2019 additional programs have been established in Canada, Australia, and, very recently, Europe. Some of these programs are focused on just 1 tumor type (eg, prostate cancer 9 ), whereas others accept a greater variety of patients. These programs may be directed by pathologists (usually), oncologists (frequently), or other researchers (occasionally), although pathologist involvement is always important for a properly executed autopsy procedure and for the selection of the best quality tissue for sampling.…”
Section: Organization Of Rapid Autopsy Programsmentioning
confidence: 99%
“…Finally, different and often unique tissue samples for multiple researchers/research projects may be collected during a single case. 9,10 Parallel specimens may be collected for the comparison of gross and microscopic pathology and for the molecular analysis of tumor clones. 11,12…”
Section: Introductionmentioning
confidence: 99%
“…As a matter of fact, next‐generation sequencing studies have shown that molecular profiles of primary tumors differ from those of their metastases, with the acquisition and loss of mutations that may confer more aggressive behavior, and therefore these profiles may lead to the development of specific therapeutic strategies . Following this rationale, a recent study described successful results with whole‐exome sequencing of postmortem samples from multiple metastatic sites obtained from a series of 15 rapid autopsies, with a time from death to the collection of material of up to 18 hours . Tumor tissue collected from these autopsies was even found to be suitable for cell cultures and RNA sequencing, with the identification of novel candidate biomarkers involved in the progression of tumors such as melanomas and ependymomas …”
mentioning
confidence: 99%
“…Following this rationale, a recent study described successful results with whole‐exome sequencing of postmortem samples from multiple metastatic sites obtained from a series of 15 rapid autopsies, with a time from death to the collection of material of up to 18 hours . Tumor tissue collected from these autopsies was even found to be suitable for cell cultures and RNA sequencing, with the identification of novel candidate biomarkers involved in the progression of tumors such as melanomas and ependymomas …”
mentioning
confidence: 99%
See 1 more Smart Citation